All‐Inorganic Perovskite Nanocrystals with Remarkably Enhanced Optoelectronic Properties Realized by an Alkene‐Free Solvent Strategy and Their Electroluminescence. Issue 6 (17th January 2022) - Dou, Yongjiang; Li, Wenqiang; Wang, Sheng; Wang, Lin; Wu, Qianqian; Luo, Yun; Li, Wei; Zhang, Jianfeng; Zhang, Jianhua; Yang, Xuyong
Abstract: Hot‐injection methods are widely used for the synthesis of colloidal perovskite nanocrystals (PeNCs). However, the long‐chain hydrocarbon solvents with alkene groups, such as octadecene (ODE), cannot be removed completely due to the strong van der Waals force between ODE and surface ligands as well as the large difference in the polarity with ethyl acetate, which hinders the charge transport characteristic of PeNCs and thus reduces the performance of PeNC‐based light‐emitting diodes (PeLEDs). Herein, an alkene‐free solvent‐assisted strategy is reported to synthesize high‐quality CsPbBr3 PeNCs in toluene and it is found that the alkene‐free solvent can significantly influence the morphology, composition, and optoelectronic properties of PeNCs. Compared to the traditional ODE solvent with alkene groups, toluene endows the higher solubility of precursors, which reduces the growth rate of PeNCs and allows sufficient time for the perovskite crystallization to suppress the bulk defects. Moreover, the similar polarity between toluene and ethyl acetate avoids long‐chain solvent residual on the PeNCs, thereby improving the charge transport characteristics. Making use of these PeNCs prepared with toluene solvent, the resulting PeLEDs present a peak external quantum efficiency of over 15%, 1.5‐fold higher than that of the device based on PeNCs that are prepared in ODE. Abstract : An alkene‐free solvent‐assisted strategy is reported to synthesize high‐quality CsPbBr3 perovskite nanocrystals (PeNCs) in toluene. The alkene‐free solvent can significantly influence the morphology, composition, and optoelectronic properties of PeNCs. The resulting PeNCs‐based light‐emitting diode presents a peak external quantum efficiency of over 15%, 1.5 times higher than that of the device based on PeNCs that are prepared in traditional octadecene.